Interpretation of natural symbols in Abdulla Aripov's poetry (Zien Journal of Social Sciences and Humanities, 2021)
In modern Uzbek poetry, the interpretation of natural symbols such as wind, rain, snow and clouds has a special place. These emblems are a figurative means of revealing the human psyche, the senses. The article reveals the symbolic meanings of wind, rain and clouds in Abdulla Aripov's works in accordance with the interpretation of spring, autumn and winter.